Análisis comparativo de la inmunocastración (GnRF) y castración quirúrgica en el rendimiento productivo en cerdos de engorde - Viscarra Vásconez, Joel Alexander (2021)
This investigative work was carried out in a documentary way; With the aim of Analyzing the effect of immunocastration (GnRF) and surgical castration on the productive performance of fattening pigs: The research had the character of a bibliographic documentary; It was developed using scientific research methods such as inductive deductive. It was carried out by reviewing, analyzing and reflecting on several scientific articles published mainly on the web; also, in books that talk about this topic. Most of them were investigated on the internet. The time that this collection of bibliographic information lasted was three months; from February to April 2021. With the information contained in this document, it is sustained that the effects of immunocastration and surgical castration, two procedures that are currently used have their benefits; They also have their own characteristics. Surgical castration demands a low cost, because it requires supplies to prevent infection, produces stress and pain in the pig; and immunocastration, does not produce pain or stress, but it is necessary to assume a higher cost, which represents the two doses of vaccines, and who applies them, implies waiting for the weight and the reasonable age of the pig for vaccination, which generally does not match in second-rate pigs. It is concluded that they are important procedures that can be used to improve the quality of the meat and eliminate the sexual smell, leaving it suitable for consumption.